Denosumab versus zoledronic acid for patients with beta-thalassemia major-induced osteoporosis - Mohamed A. Yassin (16322749) (2020)
The main aim of this study is to compare the 2 medications denosumab and zoledronic acid for patients with beta-thalassemia major induced osteoporosis. Patients with B-thalassemia major induced osteoporosis will undergo baseline assessment of the bone densitometry by bone density (DEXA) scan as a standard of care by the radiology department, then a blood test for bone-specific alkaline phosphatase and type-1 collagen telopeptide will be measured by the chemistry laboratory. Patients with B-thalassemia major induced osteoporosis, who are 18 years of age or more and willing to participate in the study will be enrolled after consenting by the primary investigator in hematology outpatient clinics. Patients with osteoporosis will receive 1 of the 2 medications; at the end of the year, DEXA scan will be done to compare the response of the 2 medications. The potential risks include drug-related side effects. The outcome will be measured biochemically by measuring bone-specific alkaline phosphatase and type 1 collagen carboxy telopeptide and radiologically by DEXA scan at baseline and 1 year using Z score. Other Information Published in: Medicine License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1097/md.0000000000023637